2013
DOI: 10.5923/j.fs.20120206.14
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of <i>Cymbopogon Citratus</i> (Lemon Grass) and It’s Phytochemical Properties

Abstract: The cold macerat ion and agar diffusion technique were emp loyed to assess phytochemical propert ies and the antimicrobial potency of Cy mbopogon citratus (lemongrass) against selected microbial pathogens using hexane, chloroform and methanol as extracting solvents. The mean zones of inhibit ion of the chloroform leaf and corresponding root extracts for the test organisms were Staphylococus aureus (11.33±1.15,11.66±2.52), Salmonella typhi (11.33±1.53,13.66±0.58), Escherichia co li (16.33±0.58,15.66±2.31) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Bioactive compounds present in C. citratus extract were assessed both qualitatively and quantitatively (TPC: Total phenolic compound). The standard protocols were used for determination of compounds such as carbohydrate, Saponin, Steroid, Phenols, Tannin, Flavonoids, Glycosides, Terpenoids, and Alkaloids (Ewansiha et al, 2012). Total phenolic content of the plant extract was determined through Folin-Ciocalteu reagent (Alhakmani et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioactive compounds present in C. citratus extract were assessed both qualitatively and quantitatively (TPC: Total phenolic compound). The standard protocols were used for determination of compounds such as carbohydrate, Saponin, Steroid, Phenols, Tannin, Flavonoids, Glycosides, Terpenoids, and Alkaloids (Ewansiha et al, 2012). Total phenolic content of the plant extract was determined through Folin-Ciocalteu reagent (Alhakmani et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…From the millennia they have been used as a potent medicinal treatment against various kinds of diseases and ailment. Plant resides wide range of bioactive components/secondary metabolites viz Phenols, Tannins, Saponin, Steriods, Alkaloids, Flavanoids, Carbohydrates and Glycosides which are responsible for antimicrobial activity (Nascimento et al, 2000; Ewansiha et al, 2012; Chaudhary et al, 2017; Elish et al, 2017) therefore the discovery of extraction of bioactive components from plants have proved to be one of the important research for human kind. Due to the negative impact of chemically designed antimicrobial drugs as compared to natural drugs on human health and environment; treatment with natural constituents has increased potentially these days (Wu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1:5) and stirred for few minutes, it was allowed to stand at room temperature for 48 hours with occasional agitation to increase penetration of solvent to the active compounds, after which the mixture was filter with muslin cloth (folded twice). The filtrates was then concentrated using water bath, dispensed in a glass bottle and stored in the refrigerator [9].…”
Section: Plant Sample Collection and Extractionmentioning
confidence: 99%
“…According to Singh et al (2011), phenolic compounds and tannins have been found to inhibit pathogenic microorganisms. Ewansiha et al (2012) mentioned that lemongrass showed antimicrobial activity against Staph. aureus, Salmonella typhi and E. coli.…”
Section: Antimicrobial Activities Of Lemongrass Extractmentioning
confidence: 99%